Pomegranate Quality from Consumers’ Perspective: Drivers of Liking, Preference Patterns, and the Relation between Sensory and Physico-Chemical Properties - Pons-Gómez, Ana; Delpozo, Bárbara; Bartual, Julián; Besada, Cristina (MDPI, 2024)
Acquiring information on consumer preferences for the sensory properties of pomegranates is a cue for breeding programmes to set their quality targets and promote the consumption of this particularly healthy fruit. In this study, a total of 12 pomegranate varieties were evaluated, including commercial (Valenciana, Illina, Tastem, Rugalate,Wonderful, Mollar 49 y Mollar 45) and new varieties (Ref 102, Ref 383, H3/27, and D27/12). For the first time, consumers not only scored their acceptance of different pomegranate varieties but also described their sensory properties using CATA questions. This approach allowed us to identify the main drivers of liking, preference patterns, and the relationship between sensory and physico-chemical properties. Of all the sensory attributes, acidity intensity was revealed as the main driver of liking/disliking, and two different consumer preference patterns were identified: ‘low acid pomegranate lovers’ and ‘acid pomegranate lovers’. Seed properties like the intensity of woody flavour and seed/aril ratio were also key drivers for preferences. A relationship between sensory and physico-chemical properties was also established. Interestingly, sweetness perception correlated more strongly with low titratable acidity levels than with high total soluble solids levels, corroborating that acidity level is a key measurement for quality assessments. ‘H3/27’ was the most promising of the new varieties for having the well-appreciated internal properties of the ‘Mollar’ varieties and external and internal red colouration, which makes it much more appealing to consumers. This study shows that there is still room on the market for pomegranate varieties with very different sensory properties and highlights the need to develop sensory labels that help consumers make the right choices.